Targeted next-generation sequencing identified a novel variant of SOX10 in a Chinese family with Waardenburg syndrome type 2. Issue 11 (November 2020) - Liu, Xiao-Wen; Wang, Su-Yang; Xing, Zhan-Kui; Zhu, Yi-Ming; Ding, Wen-Juan; Duan, Lei; Cui, Xiao; Xu, Bai-Cheng; Li, Shu-Juan; Guo, Yu-Fen
Objective: Waardenburg syndrome type 2 (WS2) is an autosomal dominant syndrome, characterized by bright blue eyes, hearing loss, and depigmented patches of hair and skin. It exhibits high phenotypic and genetic heterogeneity. We explored the molecular etiology in a Chinese family with WS2. Methods: We recruited a three-generation family with three affected members. Medical history was obtained from all family members who underwent detailed physical examinations and audiology tests. Genomic DNA was extracted from peripheral blood of each individual, and 139 candidate genes associated with hearing loss were sequenced using Illumina HiSeq 2000 (Illumina Inc., San Diego, CA, USA) and verified by Sanger sequencing. Results: Genetic evaluation revealed a novel nonsense heterozygous variant, NM_006941.4: c.342G>A (p.Trp114Ter) in exon 2 of the SOX10 gene in the three affected patients; no unaffected family member carried the variation. We did not detect the variation in 500 Chinese individuals with normal hearing or in 122 unrelated Chinese families with hearing loss, suggesting that it was specific to our patients. Conclusions: We identified a novel heterozygous nonsense variation in a family with syndromic hearing loss and WS2. Our findings expand the pathogenic spectrum and strengthen the clinical diagnostic role of SOX10 in patients with WS2.